(untitled) (Research, Society and Development, 2021)
The peach palm fruits (Bactris gasipaes Khunt.) have a great diversity of characteristics and marketing structure in the development phase, making studies that address consumer behavior, which leads to acceptance and decision to purchase the product. The objective of the work was to characterize the profile of the consumer of fruits of this palm in the city of Belém, PA, as well as their preferences in relation to the most relevant characteristics of the fruit. Questionnaires consisting of three sets of questions were applied: social profile, consumption and attributes at the time of purchase among visitors to four most popular fairs in Belém, totaling a sample of 100 respondents. The data were submitted to statistical analysis of frequency, in addition to the global analysis of the categories to obtain the degree of importance given by the interviewees. Most of the interviewees preferred to buy fruit in clusters. The preference in the purchase periodicity was weekly (31%) and monthly (26%). The most frequent consumption habit was registered in people with average levels of education and income, characterizing them as consumers of the popular market. It can be considered that the consumer of fruits from Belém, PA prefers the purchase of fresh fruits, in clusters, of medium sizes, red peel and yellow pulp, with a soft, oily and little fibrous texture. The determining factor of purchase is the sanity and good appearance of the fruits.